Penanggulangan Pembalakan Liar dengan Hukum Pidana dan Penerapannya - Kurniawan, Wayah Aji; Kuswardani, Kuswardani (Universitas Ekasakti, 2023)
Illegal logging is an illegal practice that damages the environment, threatens the sustainability of ecosystems, and causes significant economic losses. The main aim of this research is to investigate the regulation of criminal acts and the government's efforts to overcome the impact of illegal logging. The research method used in this study is normative which analyzes library materials and laws related to illegal logging. From this study, it was found that Law no. 18 of 2013 concerning Prevention and Eradication of Forest Destruction is a regulation that is often used in enforcing illegal logging laws. The government has taken various efforts to combat illegal logging in Indonesia. One of them is granting permits for selective felling of trees in forest areas to encourage tree cutters to comply with established regulations. Apart from that, the government is also active in making regional regulations to minimize cases of illegal logging in various regions of Indonesia. Collaboration with related agencies is also part of the government's efforts to tackle illegal logging. With effective implementation, criminal law enforcement can become a strong tool in efforts to combat illegal logging. However, these efforts must be accompanied by comprehensive steps, including increasing public awareness, protecting witnesses and whistleblowers, and promoting sustainable use of forest resources.